The Influence of Midwife Performance Determinant Factors on Service Quality at Aji Batara Agung Dewa Sakti Regency Hospital, Kutai Kartanegara - Sugiyarti, Sugiyarti; Yuliaty, Farida; Asnar, Etty Sofia Mariati; Paramarta, Vip (Journal of Management and Administration Provision, 2025)
The purpose of this study is to examine the relationships between service performance and the variables of motivation, rewards, workload, supervision, and training.  This study's methodology is quantitative in nature.  A total of 36 midwives from Aji Batara Agung Dewa Sakti Hospital made up the study's sample.  Data for the study were gathered via questionnaire answers, and with the use of the SEM PLS software, SEM techniques were used for analysis.  Data analysis findings indicate that training, supervision, workload, incentives, and motivation all have a major impact on service quality.  According to this conclusion, the quality of the resultant service improves with the amount of these five variables.  Nevertheless, there is no meaningful correlation between the reward variable and service quality.  According to this study, management at Aji Batara Agung Dewa Sakti Hospital in Kutai Kartanegara Regency must give priority to managing these crucial elements in order to enhance service quality.